Long-term use of darunavir/ritonavir-containing regimens in daily practice in Belgium: retrospective observational cohort data of 1701 HIV-patients. Issue 5 (3rd September 2018) - De Wit, Stéphane; Florence, Eric; Vandekerckhove, Linos; Vandercam, Bernard; Goffard, Jean-Christophe; Van Wijngaerden, Eric; Moutschen, Michel; Demeester, Remy; Thilakarathne, Pushpike; Piryns, Hilde
Abstract: Background Once daily (QD) ritonavir or cobicistat-boosted darunavir (DRV/b), in combination with other antiretrovirals (ARVs), is recommended as a first-line option for human immunodeficiency virus-infected patients in European and USA guidelines. The objective of this study was to analyse the outcomes of DRV/r QD-based antiretroviral therapy (ART) regimens in real-life settings. Methods This is an observational, non-interventional, non-comparative, retrospective, multicentre cohort study. Data were collected from the databases of eight Belgian AIDS Reference Centres. All patients who received at least one dose of DRV/r QD, regardless of background ARV regimen, with a minimum follow-up of 6 months were included. Results Data from 1701 subjects were collected. Most were male (66.5%) with a mean age of 42.9 years, 33.1% were treatment-naïve and 66.9% were ART experienced. During a median follow-up of 2.45 years (95% CI: 1.50–3.34), the probability to remain on treatment was 87% for the first year, 79% for the second year. DRV/r was well tolerated with few discontinuations due to adverse events (6.9%) or virological failure (0.8%). Among the 1138 treatment-experienced patients, 111 (9.8%) patients received DRV/r QD monotherapy. Conclusions This retrospective cohort analysis confirms the long-term effectiveness and good tolerability of DRV/r QD in a real-life setting. No unexpected adverse events were reported.